2016
DOI: 10.1177/0738894215570429
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of domestic right-wing terrorism in the USA: Economic grievance, societal change and political resentment

Abstract: This study tests three categories of motivations for domestic right-wing terrorism in the USA: economic grievances, particularly those produced by economic restructuring; societal changes that challenge notions of white male privilege; and political and public policy elements that stoke resentments. Executing a series of negative binomial regression estimations on state-level data in the USA for the period 1970-2011, I find that measures of societal factors-specifically increase in abortion rates and growing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…Taken together, these results may explain why studies investigating the effect of economic conditions on far-right terrorism and hate crimes have insofar found mixed evidence (Soule and Dyke 1999;Falk et al 2011;Dustmann et al 2011;Green et al 1998a, b;Piazza 2017;Freilich et al 2015a). Indeed, most of this research has focused on short-term or absolute indicators of deprivation at the state-level, instead of long-term national variations.…”
Section: Robustness Checksmentioning
confidence: 91%
See 2 more Smart Citations
“…Taken together, these results may explain why studies investigating the effect of economic conditions on far-right terrorism and hate crimes have insofar found mixed evidence (Soule and Dyke 1999;Falk et al 2011;Dustmann et al 2011;Green et al 1998a, b;Piazza 2017;Freilich et al 2015a). Indeed, most of this research has focused on short-term or absolute indicators of deprivation at the state-level, instead of long-term national variations.…”
Section: Robustness Checksmentioning
confidence: 91%
“…Similarly, Falk et al (2011) found that far-right extremist crimes in Germany were related to regional unemployment rate (see also Dustmann et al 2011). In contrast, other studies did not find short-term economic conditions to be consistent predictors of hate crimes and far-right offenses (Green et al 1998a;Piazza 2017;Freilich et al 2015a).…”
Section: Why Long-term Economic Variations Matter?mentioning
confidence: 94%
See 1 more Smart Citation
“…Since 2001, and the terrorist attacks on September 11, the study of radicalization and violent extremism has become a research field in its own right, in tandem with an influx of research funding on preventive interventions (Kundnani, 2012; Sedgwick, 2010). While violent religious extremism has received much attention, the past decade has seen a renewed focus on revitalized right-wing and antiglobalization violence, as well as types of violence that cut across ideological lines, such as single-issue extremism (Horgan, 2016; Piazza, 2017). Research into radicalization and violent extremism has become a field of research, rather than a subject studied within different scholarly traditions.…”
Section: Studying Radicalization and Violent Extremismmentioning
confidence: 99%
“…Writing in 2012, Jackson reiterated the overemphasis on al-Qaeda, jihadism more generally, WMDs, and the ubiquitous but poorly-understood concept of "radicalization" (See also Jackson 2012b; Schuurman and Taylor 2018). Authors have also increasingly begun to demonstrate and criticize the relative paucity of academic research on (and policymakers' attention for) the threat of right-wing extremism and terrorism (Freilich et al 2018;Koehler 2016;Manz 2018;Michael 2019;Perry and Scrivens 2016;Piazza 2017;Weinberg 2013). Another topic that has been particularly noted for its absence, especially so by scholars drawn to Critical Studies on Terrorism, is state terrorism (Dixit and Stump 2011;Silke 2019a).…”
Section: Counterterrorism By Other Means?mentioning
confidence: 99%